An Investigation of Genetic Counselors' Testing Recommendations: Pedigree Analysis and the Use of Multiplex Breast Cancer Panel Testing. Issue 4 (27th February 2014) - Lundy, Meghan G.; Forman, Andrea; Valverde, Kathleen; Kessler, Lisa
Abstract: Genetic testing recommendations for hereditary breast and ovarian cancer involve pedigree analysis and consultation of testing guidelines. The testing landscape for hereditary cancer syndromes is shifting as multiplex panel tests become more widely integrated into clinical practice. The purpose of the current study was to assess how genetic counselors utilize pedigrees to make recommendations for genetic testing, to determine consistency of these recommendations with National Comprehensive Cancer Network (NCCN) Guidelines and to explore current use of multiplex panel testing. Sixty‐nine genetic counselors were recruited through the National Society of Genetic Counselors Cancer Special Interest Group's Discussion Forum. Participation involved pedigree analysis and completion of an online questionnaire assessing testing recommendations and use of multiplex panel testing. Pedigree analysis and test recommendations were scored for consistency with NCCN guidelines. The average score was 12.83/15 indicating strong consistency with NCCN guidelines. Participants were more likely to consider multiplex testing when pedigrees demonstrated highly penetrant dominant inheritance but were not indicative of a particular syndrome. Participant concerns about multiplex panel testing include limited guidelines for both testing eligibility and medical management. This study demonstrates high utilization of pedigree analysis and raises new questions about its use in multiplex genetic testing.